Modelling Domestic Emission of City-Level Residential Area Based on Spatial Policy - Rahmah, Chania; Br Sinamo, Hediyati Anisia (Jurnal Planologi, 2025)
This study investigates the impact of spatial plan on domestic carbon emissions in the residential areas of Bandar Lampung, Indonesia, through a system dynamic modelling approach. Utilizing spatial planning policies of Bandar Lampung City and carbon emission data, the model simulates emissions from residential areas between 2014 and 2041. The research highlights how spatial plans affect high-density residential developments can slightly increase emissions. Two scenarios are analysed: one adhering to the city's spatial plan limiting building coverage ratio (BCR) to 60%, and another allowing 100% BCR, simulating a scenario with no green space. Results show a marginal increase in emissions under denser conditions, with the current policy yielding emissions of 1,422 Gg CO2 and the denser scenario producing 1,423 Gg CO2 by 2041. The study emphasizes that while spatial planning plays a role in mitigating carbon emissions, further research is needed to integrate broader land use planning elements and other urban characteristics to comprehensively address emission reduction efforts. This preliminary research offers insights into urban sustainability and policymaking, especially in the context of climate change mitigation through sustainable spatial planning.